“Honorable Toward Your Whole Self”: Experiences of the Body in Fatigued Breast Cancer Survivors - Penner, Cooper; Zimmerman, Chloe; Conboy, Lisa; Kaptchuk, Ted; Kerr, Catherine (Frontiers in Psychology, 2020)
Objective: Cancer Related Fatigue (CRF) is one of the most common and detrimental side effects of cancer treatment. Despite its increasing prevalence and severity CRF remains dismissed by the majority of clinicians. One reason for the apparent gap between clinical need and clinical undertaking is the penchant towards reductionist accounts of the disorder: a tendency to discount the interface between the lived experience of sufferers and the multi-dimensional etiology of CRF as it manifests adversely on a day-to-day basis. In order to better understand the intricacies of this lived experience we undertook semi-structured interviews with 13 Breast cancer survivors suffering from CRF and then subsequently coded their responses using Team Based Qualitative Analysis. Results: Our analysis revealed multiple dimensions of the social and bodily underpinnings of fatigue. Most relevantly we found a consistent change in the reported capacity for awareness of bodily sensations. This shift in awareness appeared to be directly connected to the experience of CRF and a newfound, “respect” for the needs of the body. Furthermore, we found that many of the practices that were described as helpful in alleviating fatigue were oriented around eliciting a sense of embodied awareness, examples being: dance, yoga, and shamanic ritual. This relationship with bodily sensations existed in conjunction with the anxiety and trauma that arose as a result of cancer treatment. Conclusion: Our analysis suggests that the quality of awareness and relationship to bodily experience in CRF is a functionally relevant component of the disorder and should be considered as an experiential target moving forward.